Strategic Sustainability Marketing Framework: Integrating Marketing Capability and Environmental Analysis in Indonesia's Glass Industry - Totok Yuliarto; Anna Wulandari; Adibah Yahya (Journal of Economics and Management, 2026)
The increasing emphasis on sustainability has encouraged manufacturing firms to reconsider how they formulate marketing strategies to support long-term organizational performance. Rather than viewing sustainability as a separate corporate initiative, firms are increasingly expected to integrate environmental considerations into strategic marketing decisions. Drawing on empirical evidence from a qualitative single-case study of a leading Indonesian glass manufacturer, this study proposes a Strategic Sustainability Marketing Framework that integrates marketing capability and strategic environmental analysis. Data were collected through semi-structured interviews, direct observation, and document analysis, complemented by strategic assessment tools including SWOT, PESTEL, and Porter’s Five Forces. The findings suggest that integrating marketing capability with systematic environmental analysis provides a conceptual basis for managerial decision-making in formulating sustainability-oriented marketing strategies. The resulting framework offers a conceptual basis for aligning internal marketing capabilities with external environmental dynamics, which may contribute to organizational adaptability, stakeholder responsiveness, and the pursuit of sustainable business performance. This study contributes to the strategic marketing and sustainability literature by offering a case-derived integrative framework for understanding sustainability-oriented marketing strategies within a dynamic manufacturing context. As the framework is derived from a single-case context, further empirical validation across diverse manufacturing sectors, geographical contexts, and methodological approaches is recommended to assess its broader applicability.